Happy Pig Day! - Willems, Mo. (New York : Hyperion Books for Children, 2011)
Piggie celebrates her favorite day of the year, but Gerald the elephant is sad, thinking that he cannot join the fun.
Ages 4-8.
Keywords: Pigs -- Fiction; Elephants -- Fiction; Parties -- Fiction; Friendship -- Fiction